تأثير التطبيقات القضائية للمحاكم الجنائية الدولية على التعامل الدولي مع جريمة الإبادة الجماعية - يتوجي, سامية (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
The International Criminal Tribunals contributed in their judicial applications with a substantial portion of the legal disclosure to the Crime of Genocide, They identified the different components of these crime especially concept, classification, and conditions related to it. By keeping track to cases of law under consideration in this article, we find that the impact levels of the International Criminal Tribunals on the Crime of genocide varied between a clear definition to the groups protected under the legal provisions to control and punishment of the Crime of Genocide, and the formulation of set of standards to determine the ethnic, religious or national groups, and the development of the mental element in the crime that put limits to the genocide intention and modes to proof its existence.